Faktor-Faktor Yang Mempengaruhi Efektivitas Penerapan Standar Akuntansi Pemerintahan Akrual Atas Barang Milik Pemerintah Daerah Kota Surabaya - Ruminingsih Ruminingsih; Ikhsan Budi Riharjo; Lilis Ardini (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
This study aims to investigate and analyze the effect of human resource competencies, organizational commitment, technology and information systems, and the intensity of stock-taking on the effectiveness of an application of accrual government accounting standards for the regional property. Therefore, a quantitative method was applied with a survey approach. This research was conducted in 72 (seventy-two) Regional Device Organizations (OPD) in Surabaya. This study used purposive sampling. The research respondents were Financial Administration Officers (PPK) and officers on goods users. As the result of statistical values, 26.9% of effective variables that applied accruals government accounting standards on the regional property could be explained with variables of human resource competence, organizational commitment, technology, and information systems, and the intensity of stock-taking. Moreover, this study indicated that human resource competence and organizational commitment had a positive effect on the application effectiveness of accrual government accounting standards for the regional property. Whereas, the technology and information systems and the intensity of stock-taking had no effect on the effectiveness of the application of accrual government accounting standards for the regional property. This study also suggested OPD within the Surabaya City Government to improve the effectiveness of the application of accrual government accounting standards for the regional property.